BARRIERS TO SURGICAL CARE ACCESS IN PAKISTAN AND THEIR IMPACT ON PATIENTS (The Research of Medical Science Review, 2025)
Background: Restricted access to surgical care is a significant determinant of increased morbidity and mortality in low- and middle-income countries (LMICs). In Pakistan, various factors such as economic constraints, lack of awareness, and inadequate healthcare infrastructure contribute to this issue. Objectives: This study aims to identify and analyze the barriers to accessing surgical care in Pakistan and their impact on patients, with a focus on understanding the delays in seeking and receiving surgical treatment. Methodology: A cross-sectional survey was conducted from February to April 2010 at Indus Hospital in Karachi, Pakistan. The study included 202 patients scheduled for elective surgeries involving general anesthesia. Data were collected using a standard questionnaire in Urdu, covering sociodemographic information, symptom severity, and reasons for delays in seeking surgical care. Statistical analysis was performed using SPSS software. Results: Out of 202 patients, 199 completed the survey. The median age was 34 years for females and 30 years for males, with 72.4% being male. The study found significant delays in seeking surgical care, with financial constraints, lack of awareness, and geographical barriers being the primary reasons. Women experienced longer delays compared to men. The median symptom duration was 7 months for women and 4 months for men. Conclusion: Barriers to accessing surgical care in Pakistan include economic constraints, lack of awareness, and geographical challenges. Addressing these issues through public education and improved healthcare infrastructure is essential to reduce delays and improve surgical outcomes.